ANÁLISIS, EN PERSPECTIVA, DE LOS CONTENIDOS DEPORTIVOS DE NOTICIAS UNO: ¿UN CAMINO HACIA LA CALIDAD INFORMATIVA EN TELEVISIÓN? - Dr. Lizandro ANGULO RINCÓN, (Fonseca, Journal of Communication, 2023)
This article analyzes the journalistic routines and the sports contents of Noticias Uno, Colombian TV news, in order to identify whether its sports information meet quality criteria. Here also consult experts for knowing their points view what it is and it should be the excellence sports journalism. For this, two sports journalistic and a group of experts are interviewed in-depth.